Kinetic Ultrasound-Assisted Extraction as a Sustainable Approach for the Recovery of Phenolics Accumulated through UVA Treatment in Strawberry By-Products - Villamil Galindo, Johan Esteban (2023)
Ultrasound-assisted extraction (UAE) is an efficient and sustainable method for extracting bioactive compounds from agro-industrial by-products. Moreover, it has been reported that ultraviolet A (UVA) radiation can induce the biosynthesis and accumulation of bioactive phenolic compounds. This study optimized the efficiency of ultrasound-assisted extraction (UAE) for recovering ultraviolet A (UVA)-induced phenolic compounds in strawberry by-products (RF-N). The impact of three factors (solid-liquid ratio, ethanol concentration, and ultrasound power) on total phenolic compound (TPC) kinetics using Peleg’s model was investigated. The developed model showed a suitable fit for both RF-N and strawberry by-products treated with UVA (RF-E). The optimal UAE conditions obtained were of a 1:30 ratio, 46% ethanol, and 100% ultrasound power, resulting in an average yield of 13 g total phenolics kg−1. The bioaccessibility of phenolic compounds during in-vitro digestion was 36.5%, with agrimoniin being the predominant compound. UAE combined with UVA treatment increased the bioactivity of RF extracts, displaying significant anti-proliferative effects on HT29 and Caco-2 cancer cell lines, as well as anti-inflammatory potential and cellular antioxidant activity. The ultrasound proved to be a sustainable and effective technique for extracting phenolic compounds from RF, contributing to the valorization of strawberry agro-industrial by-products, and maximizing their nutraceutical potential.